Application of metabolomics in viral pneumonia treatment with traditional Chinese medicine - Lili Lin; Hua Yan; Jiabin Chen; Huihui Xie; Linxiu Peng; Tong Xie; Xia Zhao; Shouchuan Wang; Jinjun Shan (BMC, 2019)
Abstract Nowadays, traditional Chinese medicines (TCMs) have been reported to provide reliable therapies for viral pneumonia, but the therapeutic mechanism remains unknown. As a systemic approach, metabolomics provides an opportunity to clarify the action mechanism of TCMs, TCM syndromes or after TCM treatment. This review aims to provide the metabolomics evidence available on TCM-based therapeutic measures against viral pneumonia. Metabolomics has been gradually applied to the efficacy evaluation of TCMs in treatment of viral pneumonia and the metabolomics analysis exhibits a systemic metabolic shift in lipid, amino acids, and energy metabolism. Currently, most studies of TCM in treatment of viral pneumonia are untargeted metabolomics and further validations on targeted metabolomics should be carried out together with molecular biology technologies.